2020
DOI: 10.1038/s41419-020-03246-7
|View full text |Cite
|
Sign up to set email alerts
|

When the chains do not break: the role of USP10 in physiology and pathology

Abstract: Deubiquitination is now understood to be as important as its partner ubiquitination for the maintenance of protein half-life, activity, and localization under both normal and pathological conditions. The enzymes that remove ubiquitin from target proteins are called deubiquitinases (DUBs) and they regulate a plethora of cellular processes. DUBs are essential enzymes that maintain intracellular protein homeostasis by recycling ubiquitin. Ubiquitination is a post-translational modification where ubiquitin molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 103 publications
(134 reference statements)
1
33
0
Order By: Relevance
“…USP10 is an important member of the ubiquitin-specific protease family, which has been found to be widely expressed in both cytoplasm and nucleus of almost all cells. As a deubiquitinating enzyme, USP10 could reverse the ubiquitination of substrates through removing ubiquitin (Ub) molecules from the C-terminal of Ub-conjugated target proteins and maintain intracellular protein homeostasis by recycling Ub [ 35 ]. Accumulating evidence demonstrated that USP10 play crucial roles as a tumor-promoter or tumor-suppressor in the tumorigenesis and development of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…USP10 is an important member of the ubiquitin-specific protease family, which has been found to be widely expressed in both cytoplasm and nucleus of almost all cells. As a deubiquitinating enzyme, USP10 could reverse the ubiquitination of substrates through removing ubiquitin (Ub) molecules from the C-terminal of Ub-conjugated target proteins and maintain intracellular protein homeostasis by recycling Ub [ 35 ]. Accumulating evidence demonstrated that USP10 play crucial roles as a tumor-promoter or tumor-suppressor in the tumorigenesis and development of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it deubiquitinates AMPK and facilitates the further activation of AMPK, forming a feedforward loop ( Hardie, 2011 ; Hornbeck et al, 2015 ). The phosphorylated Ser76 site lies in a predicted unstructured region external to the catalytic UCH domain of USP10 ( Bhattacharya et al, 2020 ). Phosphorylation may promote the activity of USP10 by inducing conformational changes in USP10 or affecting the recognition and binding of USP10 to Ub substrates.…”
Section: Ptms Can Regulate the Specificity And Activity Of Dubsmentioning
confidence: 99%
“…Moreover, Metformin, a noteworthy substance for its pharmaceutical properties, constitutes an autophagy activator [88], such as in the case of pulmonary adenocarcinoma, which undergoes apoptosis through tumor-necrosis-factor (TNF-related-Apoptosis-Inducing-Ligand (TRAIL)) [89]. For breast malignancy, in the absence of mutant BRCA1 gene, metformin can be included in therapeutic schemes with spautin-1, which constitutes an autophagy suppressor, resulting in an altered mitochondrial functional state and inducing a notable reduction incancer cell survival and progression [88,90].…”
Section: Autophagy Enhancer Agentsmentioning
confidence: 99%